Pakistan : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Pakistan's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criterion. Developments in the first months of 2002 indicate further progress toward the program's macroeconomic objectives. Progress on the structural front was broadly in line with the program, in particular in the area of tax administration, fiscal transparency, and privatization. All but one of the performance criteria for end-March 2002 were met. The authorities request a waiver for the nonobservance of the performance criterion on Central Board of Revenue (CBR) revenue.